CuInS2quantum dots embedded in Bi2WO6nanoflowers for enhanced visible light photocatalytic removal of contaminants - Luo, S.; Ke, J.; Yuan, M.; Zhang, Q.; Xie, P.; Deng, L.; Wang, Shaobin (Elsevier BV, 2018)
© 2017 Elsevier B.V. Novel CuInS 2 quantum dots (CIS-QDs)/Bi 2 WO 6 3D composites were successfully synthesized through a facile deposition process, followed by low temperature calcination. The ternary p-type CIS-QDs were highly dispersed onto the surface of flower-like n-type Bi 2 WO 6 nanosheets to form p-n heterojunction and simultaneously tune the behaviors of photogenerated charge carriers, resulting in higher photocatalytic efficiencies of toluene degradation and Cr(VI) reduction under visible light irradiation, which are 3.0 and 8.5 times higher than those of Bi 2 WO 6 , respectively. The photoelectrochemical investigations indicate that the introduction of CIS-QDs synergistically enhanced the harvesting efficiency of solar energy in the p-n heterojunction system with the internal electric field and reduced transfer barrier of photoinduced charge carriers by forming the unique Bi[sbnd]S bonds between the CIS-QDs and flower-like Bi 2 WO 6 .